Taxon-specific ultraconserved element probe design for phylogenetic analyses of scale insects (Hemiptera: Sternorrhyncha: Coccoidea) - Liu, Dajun; Niu, Minmin; Lu, Yunyun; Wei, Jiufeng; Zhang, Hufang (Frontiers in Ecology and Evolution, 2022)
Scale insects (Coccoidea) are morphologically specialized members of the order Hemiptera, with 49 families recognized to date. However, the phylogenetic relationships within and among families are poorly resolved. In this study, to further characterize the phylogenetic relationships among scale insects, an ultraconserved element (UCE) probe set was designed specifically for Coccoidea based on three low-coverage whole genome sequences along with three publicly available genomes. An in silico test including eight additional genomes was performed to evaluate the effectiveness of the probe set. Most scale insect lineages were recovered by the phylogenetic analysis. This study recovered the monophyly of neococcoids. The newly developed UCE probe set has the potential to reshape and improve our understanding of the phylogenetic relationships within and among families of scale insects at the genome level.